2000
DOI: 10.1073/pnas.97.2.835
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular protein kinase A as a cancer biomarker: Its expression by tumor cells and reversal by a myristate-lacking Cα and RIIβ subunit overexpression

Abstract: Overexpression of cAMP-dependent protein kinase (PKA) type I isozyme is associated with cell proliferation and neoplastic transformation. The presence of PKA on the external surface of LS-174T human colon carcinoma cells has been shown. Here, we show that cancer cells of various cell types excrete PKA into the conditioned medium. This extracellular PKA (ECPKA) is present in active, free catalytic subunit (C subunit) form, and its activity is specifically inhibited by PKA inhibitory protein, PKI. Overexpression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
106
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(113 citation statements)
references
References 24 publications
(22 reference statements)
6
106
0
Order By: Relevance
“…In particular, several studies support the view that R1 is related to cell proliferation whereas R2 is primarily involved in tissue differentiation (Tortora et al, 1990;Cho-Chung et al, 1995). Accordingly, in a variety of human cancer cell lines, transformation coincides with a sharp increase in R1, while R2 overexpression reverts the malignant into a non-transformed phenotype (Handschin and Eppenberger, 1979;Rohlff et al, 1993;Nesterova et al, 1996;Cho et al, 2000;Cho-Chung and Nesterova, 2005). Changes in PKA regulatory subunit expression in tumors are not exclusively due to mutational events, as demonstrated in tumoral pituitary cells that are characterized by low or absent expression of the R1A subunit protein due to proteasome-dependent protein degradation, this unbalanced expression resulting in cell proliferation (Lania et al, 2004).…”
Section: Introductionmentioning
confidence: 88%
“…In particular, several studies support the view that R1 is related to cell proliferation whereas R2 is primarily involved in tissue differentiation (Tortora et al, 1990;Cho-Chung et al, 1995). Accordingly, in a variety of human cancer cell lines, transformation coincides with a sharp increase in R1, while R2 overexpression reverts the malignant into a non-transformed phenotype (Handschin and Eppenberger, 1979;Rohlff et al, 1993;Nesterova et al, 1996;Cho et al, 2000;Cho-Chung and Nesterova, 2005). Changes in PKA regulatory subunit expression in tumors are not exclusively due to mutational events, as demonstrated in tumoral pituitary cells that are characterized by low or absent expression of the R1A subunit protein due to proteasome-dependent protein degradation, this unbalanced expression resulting in cell proliferation (Lania et al, 2004).…”
Section: Introductionmentioning
confidence: 88%
“…In particular, in contrast to the recent observation that loss of PKRAR1A was associated with multiple neoplasia, previous studies carried out on human cancers and cell lines, such as breast, colon and lung carcinomas, fibrosarcomas, gliomas, and leukemias, indicated that R1 was the major or the sole R subunit detectable and was primarily involved in cell proliferation (6, 7, 24 -26). Conversely, R2 would be related to tissue differentiation and the induction of R2 subunits by 8-Cl-cAMP treatment in malignant cell lines was associated with growth arrest and reversion of the transformed phenotype (5,8,9,27).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, previous studies supported the view that R1 was related to cell proliferation whereas R2 was primarily involved in tissue differentiation (4 -6). Accordingly, in a variety of human cancer cell lines, transformation coincides with a sharp increase in R1, whereas R2 overexpression reverts the malignant phenotype into a nontransformed phenotype (7)(8)(9). However, the involvement of R1 in promoting cell proliferation and transformation has been challenged by the recent identification of R1A gene (PRKAR1A) mutations causing the loss of R1 expression and function in patients with Carney complex, a familial multiple neoplasia syndrome characterized by the association of skin pigmentation, cardiac myxomas and different endocrine tumors, including growth hormone (GH)-secreting pituitary tumors (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, overexpression of the inducible repressor, ICERII␥, in endocrine and neuroendocrine cancers alters the growth of these tumors (30). Also, PKA, a cAMP-dependent kinase, is implicated in different types of cancer (31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%